DESIGN AND FABRICATION OF FOOT PEDAL OPERATED BLACK SMITHY HAMMER - Adarsh Sameer Gangawane; Priyanka Nanasaheb Kardile (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
A hammer is one of the important tools used by the blacksmiths. It is a force multiplier that works by converting mechanical work into kinetic energy. It is a device that delivers a blow i.e. a sudden impact on object.Most of the hammers are hand tools used for bending, hammering, forging, breaking a part, etc. This hand hammers require more effort, also may sometimes deviate from the target, where it is required to hit the object and cause injury to the operator. In our device we made such an arrangement that the hammer can be operated with a foot. It works on a basic principle of four bar chain mechanism. It is a great tool for single blow with a fair bit of power for light swaging that we cannot do with a hand hammer. They are also great for the fact that it frees up your hand to hold the job. Hereby the operator can firmly handle the job which avoids falling of tools or hot workpiece on leg and avoids injury. It perfectly delivers the impact on the workpiece and at the target desired by the operator. It proves to be suitable and effective for making lot of stuff which does not require continuous blows but rather needs a striker to pound it. As compared to hand hammers it relatively takes less time to complete the jobs and hereby it improves the efficiency and increases productivity.